Access granted: Open publishing – An interview with Wendy Taylor & Tracy Breheny - Wiktoria Wisniewska, Wendy Taylor, Tracy Breheny (BioScientist: The Salford Biomedicine Society Magazine, 2024)
The ‘BioScientist’ magazine is a fully open access journal available on the Salford Open Journals platform, led for students, by students. Our Co-Editor-in-Chief Wiktoria Wisniewska had the pleasure to interview Wendy Taylor, an Open Research Coordinator at the University of Salford, and Tracy Breheny, Academic Support Librarian, about open access publishing and its benefits for scientific communication and student learning. The Editorial Team would like to thank Assoc Prof Robin Beck for connecting us with Wendy and Tracy, the Featured Collaborators for this article.